Bewehrungsstrategien für den Beton‐3D‐Druck. Issue 8 (6th July 2020) - Kloft, Harald; Empelmann, Martin; Hack, Norman; Herrmann, Eric; Lowke, Dirk
Abstract: Die Stahlbetonbauweise wurde in ihren Anfängen mit ingeniösen, materialsparenden Konstruktionen verbunden, entworfen aus dem Verständnis des kongenialen Zusammenwirkens der beiden Werkstoffe Beton und Stahl. Heutzutage ist Stahlbeton das am meisten eingesetzte Material im Bauwesen. Durch den Einsatz von Systemschalungen und einfach zu verlegenden Flächenbewehrungen werden Baukonstruktionen gefördert, die in Bezug auf Lohnkosten optimiert sind, aber oftmals eine ineffiziente Materialausnutzung aufweisen. Stefan Polónyi hat in diesem Zusammenhang immer wieder das mangelnde Verständnis der Ingenieure für das Zusammenwirken von Beton und Bewehrung kritisiert. Mit dem Beton‐3D‐Druck steht eine digitale Fertigungstechnologie bereit, die eine neue Gestaltungsfreiheit im Betonbau ermöglicht bei gleichzeitig ressourceneffizientem Materialeinsatz. Für die Integration der Bewehrung besteht die Chance für eine kraftflussgesteuerte Führung in den zugbeanspruchten Bereichen. Dies erfordert neue Strategien für die kombinierte Additive Fertigung von Beton und Bewehrung. Abstract: Strategies for the reinforcement for 3D‐concrete‐printing The ingenious bridge, hall and shell structures of the last century were designed from the understanding of the congenial interaction of the two materials concrete and steel. Nowadays, reinforced concrete is the most widley used material in construction. The use of system formwork and easy‐to‐install reinforcement support structures that are optimized in terms of labor costs, but often have an inefficient use of material. In this context, Stefan Polónyi has repeatedly criticised the engineerś lost understanding of the interaction of concrete and reinforcement. With Additive Manufacturing, an innovative digital manufacturing technology is now available that allows new freedom in concrete design while at the same time making resource‐efficient use of materials. With regard to practical application, the integration of reinforcement represents a central challenge in 3D‐concrete‐printing. The authors see here the future chance of a force‐flow controlled reinforcement layout. The paper shows new strategies for the combined additive manufacturing of concrete and reinforcement and presents first 3D‐printed reinforced concrete elements.